Silica-based scale adhesion inhibitor and method for preventing silica-based scale adhesion
A copolymer of (meth)acrylic acid and phosphoric acid effectively prevents silica-based scale adhesion in high-silica aqueous systems, addressing the limitations of existing inhibitors by reducing scale formation and maintaining system efficiency.
Patent Information
- Application Number
- JP2020168095
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-10-02
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2040-10-02
AI Technical Summary
Existing silica-based scale inhibitors are ineffective in preventing silica-based scale adhesion in aqueous systems with silica concentrations exceeding 150 ppm, particularly in systems containing calcium, magnesium, aluminum, iron, and zinc, leading to significant adhesion and cleaning difficulties.
A copolymer containing (meth)acrylic acid and a specific structural unit, combined with phosphoric acid and/or its salt, is used to inhibit silica-based scale adhesion in silica-containing aqueous systems, maintaining a weight ratio of 50:1 to 1:5, effectively preventing scale formation even at high silica concentrations.
The copolymer and phosphoric acid combination significantly reduces silica-based scale adhesion in cooling water systems, preventing both amorphous silica and silicate scale formation, even in harsh conditions with high silica and metal ion concentrations, while avoiding the generation of other scales like calcium or magnesium phosphates.
Smart Images

Figure 0007617550000014 
Figure 0007617550000001 
Figure 0007617550000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a silica-based scale adhesion preventive agent and a method for preventing silica-based scale adhesion, which are capable of preventing the occurrence of silica-based scale troubles in a silica-containing aqueous system that contains silica in the water. [Background technology]
[0002] Heat transfer surfaces and piping in contact with cooling water in cooling water systems, boiler water systems, geothermal power generation water systems, etc. are prone to scaling problems. In particular, in open circulation cooling water systems, from the viewpoint of resource and energy conservation, the amount of cooling water discharged (blow amount) is sometimes limited and highly concentrated operation is performed, and salts dissolved in the water are concentrated to form sparingly soluble salts and scale, which is likely to cause scaling problems. Since scaling causes serious problems in the operation of equipment, such as reduced thermal efficiency and blockages in heat exchangers and piping, measures against it are required.
[0003] Examples of scale types that cause general scale problems include calcium carbonate, calcium sulfate, calcium sulfite, calcium phosphate, magnesium hydroxide, zinc phosphate, zinc hydroxide, etc. These general scale problems can be solved by adding water-soluble polymers of acrylic acid or maleic acid, or organic phosphonic acids such as hydroxyethylidenediphosphonic acid and phosphonobutanetricarboxylic acid to the aqueous system, and scale inhibitors for the above scale types are widely and commonly used.
[0004] In recent years, silica-based scale damage is becoming more likely to occur due to the high concentration of components in water caused by the reuse of industrial water, for example, the high concentration of cooling water as mentioned above, and this has become a problem. In addition, high concentrations of carbon dioxide gas and hydrogen sulfide gas are ejected from the steam wells of geothermal power plants along with steam and hot water, and the hot water contains a lot of silica. This causes silica-based scale damage by polymerizing inside pipes, reinjection wells, boilers, etc. Therefore, measures against silica-based scale are required in addition to cooling water systems. Silica-based scale includes amorphous silica and silicate scale. Amorphous silica is non-crystalline silica-based scale that occurs when silica alone exceeds its solubility. Silicate scale is silica contained in water that is combined with metal ions such as calcium ions, magnesium ions, and aluminum ions to form poorly soluble silicate scale such as calcium silicate, magnesium silicate, and aluminum silicate. Silicate scale also includes composites of the above silicates with poorly soluble inorganic compounds such as amorphous silica, calcium carbonate, and calcium phosphate. Generally, silica has low solubility and has the tendency to cause scaling in cooling water systems even at silica concentrations of around 100 to 150 ppm. Currently, in cooling water systems, the upper limit of the concentration of cooling water is set based on the silica concentration in the water.
[0005] It is also known that the presence of calcium, magnesium, aluminum, iron, zinc, etc. in water promotes the precipitation of silica. Therefore, in cooling water systems in which silica, calcium, magnesium, aluminum, iron, zinc, etc. are present in the water, the silica concentration in the water must be further reduced and precisely controlled. Due to its nature, once silica-based scale adheres to equipment, etc., it is very difficult to wash and remove it, so it is considered important to prevent the adhesion of scale in advance.
[0006] Here, there are several proposals for scale inhibitors against silica-based scale. For example, there are a scale inhibitor containing an acrylamide polymer and an acrylic acid polymer (Patent Document 1), a scale inhibitor containing a polymeric nonionic surfactant obtained by adding an alkylene oxide to the active hydrogen of a primary and / or secondary amine of polyethyleneimine (Patent Document 2), a silica-based scale inhibitor containing an alkyl group (having 12 to 18 carbon atoms) or an alkenyl group (having 12 to 18 carbon atoms) ether or ester of a polyalkylene glycol, which is a general nonionic surfactant (Patent Document 3), and a scale inhibitor containing a polyethylene glycol having a molecular weight of 1000 to 100,000 and a phosphonic acid and / or a carboxylic acid polymer having a molecular weight of 100,000 or less (Patent Document 4). For the scale inhibitors disclosed in Patent Document 1 and Patent Document 2, tests on scale adhesion to the surface of heat exchangers have been carried out. However, for the scale inhibitor disclosed in Patent Document 1, only the scale prevention effect in an aqueous system with a silica concentration of 150 mg / L has been demonstrated, and it is unclear whether the same scale prevention effect will be exhibited in an aqueous system with a higher silica concentration. In addition, for the scale inhibitor disclosed in Patent Document 2, the scale adhesion rate (mg / cm 2 / month) was 12 to 100, and it cannot be said that a sufficient effect of preventing scale adhesion was obtained. Furthermore, for the silica scale inhibitor disclosed in Patent Document 3, the effect of improving silica solubility in water is shown, but there is no mention of the effect of preventing adhesion of silica-based scale. Furthermore, for the scale inhibitor disclosed in Patent Document 4, although the effect of suppressing scale precipitation and the effect of preventing scale adhesion in a test solution with a silica concentration of 350 ppm are shown, the test time is short, and it is unclear whether the effect of preventing scale adhesion is at a level applicable to an actual machine. Therefore, there is room for further investigation into a silica-based scale deposition inhibitor that exhibits a sufficient silica-based scale deposition inhibitory effect in silica-containing aqueous systems in which deposition of silica-based scale that exceeds the solubility of silica ions is likely to occur.
[0007] In addition, a copolymer of (meth)acrylic acid / (meth)acrylamidomethylpropanesulfonic acid or styrene acid / (meth)acrylamide or substituted (meth)acrylamide has been disclosed as a scale inhibitor for silica-based scale (Patent Document 5). However, this scale inhibitor did not show sufficient silica-based scale adhesion prevention effect in cooling water systems with a silica concentration of, for example, 150 ppm or more (silica-containing water systems in which silica-based scale adhesion is likely to occur because the silica concentration exceeds the solubility of silica ions). Furthermore, in severe conditions in which silica-based scale adhesion is likely to occur due to the presence of calcium, magnesium, aluminum, iron, zinc, etc. in addition to silica in the water, even the use of the above-mentioned scale inhibitor did not provide sufficient scale adhesion prevention effect. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Patent No. 1851103 [Patent Document 2] Patent No. 2974378 [Patent Document 3] Japanese Patent Application Publication No. 58-84098 [Patent Document 4] Japanese Patent Application Publication No. 2-31894 [Patent Document 5] Patent No. 3055815 [Patent Document 6] JP 2017-72122 A Summary of the Invention [Problem to be solved by the invention]
[0009] Water used in cooling water systems, boiler water systems, geothermal power generation water systems, etc. is usually industrial water, tap water, groundwater, etc., and therefore various types of scale are present in the water. In particular, when handling an aqueous system containing silica in the water, problems with silica-based scale damage occur, and particularly when a highly concentrated aqueous system containing silica is operated, silica-based scale damage is likely to occur. Therefore, there is a demand for a silica-based scale adhesion inhibitor and a silica-based scale adhesion prevention method that are useful for preventing the adhesion of silica-based scale.
[0010] The effect of the agent is to improve the solubility of silica ions in water and inhibit the deposition of silica scale, which is different from the effect of preventing the adhesion of silica-based scale. When the silica concentration in water exceeds the solubility, silica-based scale begins to form polymerized silicic acid, and co-deposition with other scale components in the water (calcium, magnesium, aluminum, iron, zinc, etc.) begins, causing the deposition of silica-based scale. Generally, the SiO 2 concentration at 25°C is 2 Since the solubility of silica is about 150 ppm, it is believed that silica-based scale is likely to form when the silica concentration is 150 ppm or more. On the other hand, whether or not silica in water or precipitated silica-based scale adheres to equipment such as condensers, heat exchangers, and piping must be confirmed including different factors such as the environmental aspects of the surfaces of the equipment such as condensers, heat exchangers, and piping that are the targets of adhesion. This is because even if silica-based scale precipitation is not observed in the water, silica-based scale adhesion may occur on the above-mentioned objects, and conversely, even if silica-based scale is precipitated in the water, silica-based scale may not adhere to the objects. This is thought to be related to silica dissolved or precipitated in water, and the surface temperature, surface environment (pH, etc.) and surface charge of the target. For example, Patent Document 6 discloses a silica-based scale adhesion prevention device, and SiO 2 The silicate tetrahedron (SiO 4) and combines with cations to prevent the deposition of silica scale on negatively charged condensers, water supply pipes, etc. This document also shows that the formation of silica scale is considered to be a phenomenon that cannot be explained solely by an inorganic chemical model defined by solubility and chemical equilibrium.
[0011] In view of the above-mentioned circumstances, an object of the present invention is to provide a silica-based scale deposition preventive agent and a silica-based scale deposition preventive method that are useful for preventing deposition of silica-based scale that occurs in a silica-containing aqueous system that contains silica in water. [Means for solving the problem]
[0012] The present inventors have found that by using copolymer (A) containing (meth)acrylic acid, a structural unit represented by general formula (1) and a structural unit represented by general formula (2) and / or copolymer (B) containing (meth)acrylic acid and a structural unit represented by general formula (1) in combination with phosphoric acid and / or a salt thereof, deposition of silica-based scale can be effectively prevented in silica-containing aqueous systems that contain silica, particularly silica-containing cooling water systems and silica-containing aqueous systems that contain calcium, magnesium, aluminum, iron, zinc and the like in addition to silica and are prone to formation of silica-based scale.
[0013] The present invention comprises a copolymer (A) and / or a copolymer (B), and phosphoric acid and / or a salt thereof, wherein the copolymer (A) is a copolymer containing (meth)acrylic acid, a structural unit represented by the following general formula (1), and a structural unit represented by the following general formula (2): The copolymer (B) is a silica-based scale preventive agent characterized in that it is a copolymer containing (meth)acrylic acid and a structural unit represented by the following general formula (1).
[0014] [ka] (In the formula, R 1 is H or COOX, X is H or a metal cation, and R 2 and R3 is H or C 1-8 The alkyl groups are either H or CH. 3 It is.)
[0015] [ka] (Wherein, R is H or CH 3 X is H or a metal cation; R 4 is C 1-8 is an alkyl group or a phenyl group, and R 5 is H or C 1-4 It is an alkyl group. In the silica-based scale preventive agent of the present invention, the content weight ratio of copolymer (A) and / or copolymer (B) to phosphoric acid and / or a salt thereof is preferably 50:1 to 1:5.
[0016] The present invention also relates to a method for preventing silica-based scale deposition, which comprises using the above-mentioned silica-based scale inhibitor in a silica-containing aqueous system.
[0017] The present invention also relates to a method for preventing silica-based scale adhesion, comprising a copolymer adding step of adding copolymer (A) and / or copolymer (B) to a silica-containing aqueous system, and a phosphoric acid, etc. adding step of adding phosphoric acid and / or a salt thereof, wherein the copolymer (A) is a copolymer containing (meth)acrylic acid, a structural unit represented by the general formula (1) above, and a structural unit represented by the general formula (2) above, and the copolymer (B) is a copolymer containing (meth)acrylic acid and a structural unit represented by the general formula (1) above. In the method for preventing silica-based scale adhesion of the present invention, the weight ratio of the copolymer (A) and / or the copolymer (B) added in the copolymer adding step to the phosphoric acid and / or a salt thereof added in the phosphoric acid etc. adding step is preferably 50:1 to 1:5. In the method for preventing silica-based scale adhesion of the present invention, in the phosphoric acid or the like addition step, phosphoric acid and / or a salt thereof is preferably added so that the ratio of silica concentration to phosphoric acid concentration (silica concentration:phosphoric acid concentration) in the silica-containing aqueous system is 25:1 to 300:1. Effect of the Invention
[0018] According to the present invention, it is possible to provide a silica-based scale deposition inhibitor and a silica-based scale deposition prevention method which can extremely effectively prevent the deposition of silica-based scale that occurs in silica-containing water systems, and which is particularly useful for preventing the deposition of silica-based scale that occurs in silica-containing cooling water systems and silica-containing water systems that contain silica, calcium, magnesium, aluminum, iron, zinc, etc. [Brief description of the drawings]
[0019] [Figure 1] FIG. 1 is a schematic diagram of a cooling water system used in the evaluation of silica-based scale damage. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] Hereinafter, the present invention will be described in detail based on embodiments. The silica-based scale adhesion preventive agent of the present invention contains copolymer (A) and / or copolymer (B) and phosphoric acid and / or a salt thereof, wherein the copolymer (A) is a copolymer containing (meth)acrylic acid, a structural unit represented by the following general formula (1) and a structural unit represented by the following general formula (2), and the copolymer (B) is a copolymer containing (meth)acrylic acid and a structural unit represented by the following general formula (1). Here, (meth)acrylic means acrylic or methacrylic.
[0021] [ka] (In the formula, R 1 is H or COOX, X is H or a metal cation, and R 2 and R 3 is H or C 1-8The alkyl groups are either H or CH. 3 It is.)
[0022] [ka] (Wherein, R is H or CH 3 X is H or a metal cation; R 4 is C 1-8 is an alkyl group or a phenyl group, and R 5 is H or C 1-4 It is an alkyl group.
[0023] The copolymer (A) is a copolymer containing (meth)acrylic acid, a structural unit represented by general formula (1) and a structural unit represented by general formula (2), and is a polymer already known to be used as a silica-based scale adhesion inhibitor (see Patent Document 5). However, the copolymer (A) alone did not show sufficient silica-based scale adhesion prevention effect in a silica-containing aqueous system having a silica concentration of 150 ppm or more. That is, from the viewpoint of preventing silica-based scale adhesion, the use of the copolymer (A) alone was not sufficient to prevent silica-based scale adhesion in a silica-containing aqueous system. However, surprisingly, by using the copolymer (A) in combination with phosphoric acid and / or a salt thereof, it was possible to sufficiently prevent silica-based scale adhesion even in a silica-containing aqueous system in which silica-based scale adhesion is likely to occur in excess of the solubility of silica ions, for example, in a silica-containing aqueous system in which the silica concentration is 150 ppm or more at room temperature. The present invention was completed based on the above findings found by the present inventors.
[0024] As described above, the water used in the water system is usually industrial water, tap water, or groundwater, and various scale species are present in the water in an ionized state. In general, the water used in cooling water, boiler water systems, and geothermal power generation water systems contains calcium, magnesium, aluminum, iron, and / or zinc as water components in addition to silica. When water containing such components is concentrated by recycling or reusing, not only the silica component but also other components are concentrated and become highly concentrated. Here, when phosphoric acid is added to an aqueous system in which the concentration of aqueous components such as calcium and magnesium is high, scale such as calcium phosphate and magnesium phosphate is generated, and therefore, adding phosphoric acid and / or its salts to highly concentrated water has not been practiced in the past (References: JP-A-07-256266, JP-A-2015-8568, Zairyo-to-Kankyo, 42, 442-450 (1993) Vol. 42, No. 7, Materials and the Environment, 64, 114-120 (2015) Vol. 64, No. 4).
[0025] However, the present inventors have studied prevention of silica-based scale deposition in silica-containing aqueous systems that contain calcium, magnesium, and the like in addition to silica, such as aqueous systems having a silica concentration of 150 ppm or more at room temperature, in which deposition of silica-based scale exceeding the solubility of silica ions is likely to occur. As a result, they have unexpectedly found that by using the above-mentioned copolymer (A) and / or the above-mentioned copolymer (B) in combination with phosphoric acid and / or a salt thereof, a sufficient silica-based scale deposition prevention effect can be achieved without inviting the generation of other calcium phosphates or magnesium phosphates, even in silica-containing aqueous systems having a silica concentration of 150 ppm or more and containing calcium, magnesium, and the like. As a result, the inventors have discovered that the scale adhesion inhibitor of the present invention is extremely useful for preventing the adhesion of silica-based scale that occurs in silica-containing aqueous systems in which the adhesion of silica-based scale exceeds the solubility of silica ions and that occur under severe conditions including aqueous systems containing calcium, magnesium, aluminum, iron, zinc, etc.
[0026] In the present invention, the silica-based scale includes amorphous silica and silicate scale. Amorphous silica is non-crystalline silica-based scale that occurs when silica alone exceeds its solubility. Meanwhile, silicate scale is silica contained in water that is combined with metal ions such as calcium ions, magnesium ions, and aluminum ions to become sparingly soluble silicate scale such as calcium silicate, magnesium silicate, and aluminum silicate. Furthermore, silicate scale also includes composites of the above silicates with sparingly soluble inorganic compounds such as the above amorphous silica, calcium carbonate, and calcium phosphate. Silica-containing aqueous systems that contain not only silica but also metals such as calcium, magnesium, aluminum, iron, and zinc can be said to have water quality conditions that are more severe than those of silica-containing aqueous systems that do not contain these metals, making them more susceptible to the deposition of silica-based scale. The silica-based scale inhibitor of the present invention has a sufficient effect of preventing scale buildup caused by both amorphous silica and silicate scale.
[0027] The copolymer (A) in the silica-based scale preventive agent of the present invention is a copolymer containing (meth)acrylic acid, a structural unit represented by general formula (1), and a structural unit represented by general formula (2). The weight average molecular weight of the copolymer (A) is preferably 1000 to 25000. In addition, it is preferable that the total amount of the copolymer (A) is 100% by weight, and the copolymer (A) contains 15 to 90% by weight of (meth)acrylic acid, 5 to 30% by weight of the structural unit represented by general formula (1), and 5 to 80% by weight of the structural unit represented by general formula (2). The weight average molecular weight of the copolymer (A) is preferably from 2,000 to 20,000, and more preferably from 3,000 to 15,000. It is more preferable that, relative to 100% by weight of the total amount of copolymer (A), the (meth)acrylic acid content is 25 to 90% by weight, the structural unit represented by general formula (1) is 5 to 25% by weight, and the structural unit represented by general formula (2) is 5 to 70% by weight.
[0028] Moreover, the copolymer (B) in the silica-based scale preventive agent of the present invention is a copolymer containing (meth)acrylic acid and a structural unit represented by the following general formula (1). The weight average molecular weight of the copolymer (B) is preferably 1000 to 20000. Moreover, it is preferable that, relative to 100% by weight of the total amount of the copolymer (B), the content of (meth)acrylic acid is 60 to 95% by weight, and the content of the structural unit represented by the general formula (1) is 5 to 40% by weight. The weight average molecular weight of the copolymer (B) is preferably from 2,000 to 20,000, and more preferably from 3,000 to 15,000. It is more preferable that the (meth)acrylic acid content is 70 to 95% by weight and the structural unit represented by the general formula (1) is 5 to 30% by weight, based on 100% by weight of the total amount of the copolymer (B).
[0029] The weight average molecular weight (hereinafter also referred to as Mw) of the copolymer (A) and / or the copolymer (B) can be calculated from the value measured by gel permeation chromatography (hereinafter also referred to as GFC). The measurement conditions of GFC for each structural unit can be as follows.
[0030] <Copolymer (A) and / or Copolymer (B)> Equipment: Shimadzu Prominence Column: Shodex OHpakSD-G+SB-805HQ+SB-804HQ Measurement temperature: 40℃ Solution injection volume: 100μL Detector: Differential refractometer (RI) Reference material: PEO
[0031] In the structural unit represented by the above general formula (1), R 2 and R 3 is either a hydrogen atom or an alkyl group having 1 to 8 carbon atoms, while R 2 and R 3None of the above can be a hydrogen atom. The alkyl group having 1 to 8 carbon atoms is not particularly limited as long as the total number of carbon atoms is 1 to 8, but the number of carbon atoms is preferably 1 to 4. In addition, the structural unit represented by the above general formula (1) is preferably tert-butylacrylamide and / or isopropylacrylamide.
[0032] In the structural unit represented by the above general formula (2), R 4 is an alkyl group or a phenyl group having 1 to 8 carbon atoms, and is not particularly limited as long as the total carbon number is 1 to 8, but preferably has 2 to 8 carbon atoms. 5 is a hydrogen atom or an alkyl group having 1 to 4 carbon atoms, and is not particularly limited as long as the total number of carbon atoms is 1 to 4. As the structural unit represented by the above general formula (2), 2-acrylamido-2-methylpropanesulfonic acid (AMPS) is preferred.
[0033] The copolymer (A) is preferably an acrylic acid / N-tert-butylacrylamide / 2-acrylamido-2-methylpropanesulfonic acid (AMPS) copolymer, and the copolymer (B) is preferably an acrylic acid / N-tert-butylacrylamide copolymer, because this can effectively prevent the generation of silica-based scale in silica-containing water.
[0034] The silica-based scale preventive agent of the present invention preferably contains a copolymer (A).
[0035] The phosphoric acid and / or salt thereof in the silica-based scale adhesion preventive agent of the present invention does not include polymerized phosphoric acid and / or salt thereof, condensed phosphoric acid and / or salt thereof, and phosphorus compounds. As the phosphoric acid and / or salt thereof in the present invention, for example, phosphoric acid, sodium phosphate, and other commonly used ones can be used, but are not limited thereto. As the phosphoric acid and / or salt thereof in the present invention, it is preferable to use at least one selected from the group consisting of phosphoric acid and sodium phosphate. This is because the generation of silica-based scale in silica-containing water can be effectively prevented.
[0036] In the silica-based scale adhesion preventive agent of the present invention, the content weight ratio of the copolymer (A) and / or the copolymer (B) to phosphoric acid and / or a salt thereof is preferably 50: 1 to 1: 5. When the content weight ratio of the copolymer (A) and / or the copolymer (B) to phosphoric acid and / or a salt thereof is within the above range, the generation of silica-based scale in silica-containing water can be effectively prevented. The weight ratio of the copolymer (A) and / or the copolymer (B) to the phosphoric acid and / or a salt thereof is more preferably 30:1 to 1:5, and further preferably 30:1 to 1:1.5.
[0037] In addition, the silica-based scale adhesion preventive agent of the present invention preferably further contains a copolymer (C) containing (meth)acrylic acid and a structural unit represented by general formula (2). By further containing the copolymer (C), the occurrence of silica-based scale in a silica-containing aqueous system can be more effectively prevented. The copolymer (C) is preferably an acrylic acid-AMPS copolymer. When the silica-based scale adhesion preventive agent of the present invention contains the copolymer (C), the content of the copolymer (C) is preferably 1 to 49% by weight, and more preferably 5 to 30% by weight, relative to 100% by weight of the total amount of the silica-based scale adhesion preventive agent.
[0038] In addition, the silica-based scale adhesion preventive agent of the present invention is preferably used in an aqueous system that exceeds the solubility of silica ions. For example, the solubility of silica is SiO 2As a result, the silica-based scale adhesion inhibitor of the present invention is preferably used in a silica-containing aqueous system having a silica concentration of 150 ppm or more, and more preferably in a silica-containing aqueous system having a silica concentration of more than 150 ppm. In a silica-containing aqueous system having a silica concentration of 150 ppm or more, a commonly known silica-based scale adhesion inhibitor may not exhibit a sufficient silica-based scale adhesion prevention effect, but the silica-based scale adhesion inhibitor of the present invention exhibits a sufficient silica-based scale adhesion prevention effect even in an aqueous system having a silica concentration of 150 ppm or more. Furthermore, the silica-based scale adhesion inhibitor of the present invention exhibits a sufficient silica-based scale adhesion prevention effect even in an aqueous system having a silica concentration of more than 150 ppm. The silica concentration of the silica-containing aqueous system to which the silica-based scale preventive agent of the present invention is applied is more preferably 170 ppm or more, and even more preferably 200 ppm or more. In the present invention, the solubility of silica ions is SiO 2 is the solubility as
[0039] The present invention also relates to a method for preventing silica-based scale deposition, which comprises using the silica-based scale inhibitor of the present invention.
[0040] In another embodiment, the present invention also relates to a method for preventing silica-based scale adhesion, comprising a copolymer addition step of adding (meth)acrylic acid, a copolymer (A) having structural units represented by general formulas (1) and (2), and / or a copolymer (B) having structural units represented by (meth)acrylic acid and general formula (1) to a silica-containing aqueous system, and a phosphoric acid etc. addition step of adding phosphoric acid and / or a salt thereof.
[0041] In the method for preventing silica-based scale adhesion of the present invention, the content weight ratio of the copolymer (A) and / or copolymer (B) added in the copolymer adding step to the phosphoric acid and / or a salt thereof added in the phosphoric acid etc. adding step is preferably 50:1 to 1:15, more preferably 50:1 to 1:5, because this allows effective prevention of silica-based scale adhesion in silica-containing water. In the above copolymer addition step, when copolymer (A) and copolymer (B) are added, the copolymer weight is the total weight of copolymer (A) and copolymer (B). In the above phosphoric acid etc. addition step, when phosphoric acid and a phosphate are added, the phosphoric acid etc. weight is the total weight of phosphoric acid and a phosphate.
[0042] In the phosphoric acid or the like addition step of the method for preventing silica-based scale adhesion of the present invention, it is preferable to add phosphoric acid and / or a salt thereof so that the ratio of silica concentration to phosphoric acid concentration (silica concentration:phosphoric acid concentration) in the silica-containing water system is 25:1 to 300:1, because this makes it possible to effectively prevent adhesion of silica-based scale in the silica-containing water.
[0043] The silica-containing aqueous system in the method for preventing silica-based scale adhesion of the present invention is preferably an aqueous system containing silica exceeding the solubility of silica ions. This is because, while a method for preventing silica-based scale adhesion using a commonly known silica-based scale adhesion inhibitor often does not exhibit a sufficient silica-based scale adhesion prevention effect in an aqueous system exceeding the solubility of silica ions, the method for preventing silica-based scale adhesion of the present invention exhibits a sufficient silica-based scale adhesion prevention effect in an aqueous system exceeding the solubility of silica ions.
[0044] The silica-containing aqueous system in the method for preventing silica-based scale adhesion of the present invention is preferably an aqueous system having a silica concentration of 150 ppm or more. This is because, while a method for preventing silica-based scale adhesion using a commonly known agent for preventing silica-based scale adhesion often does not exhibit a sufficient effect of preventing silica-based scale adhesion in an aqueous system having a silica concentration of 150 ppm or more, the method for preventing silica-based scale adhesion of the present invention exhibits a sufficient effect of preventing silica-based scale adhesion in an aqueous system having a silica concentration of 150 ppm or more.
[0045] In addition, the preferred embodiments of the copolymer (A) and the copolymer (B), the preferred embodiments of the phosphoric acid and / or a salt thereof, and the compounding ratio thereof in the above-mentioned method for preventing silica-based scale adhesion are the same as those in the above-mentioned silica-based scale adhesion preventive agent of the present invention.
[0046] In addition, in the method for preventing silica-based scale adhesion of the present invention, the concentration of copolymer (A) and / or copolymer (B) in the silica-containing water after the copolymer addition step is preferably 1 to 50 mg / L, more preferably 2 to 25 mg / L. This is because the scale adhesion inhibitor of the present invention, or copolymer (A) and / or copolymer (B) is added so that the concentration of copolymer (A) and / or copolymer (B) in water falls within the above range, thereby making it possible to suitably prevent adhesion of silica-based scale in a silica-containing water system. The amount of the silica-based scale adhesion inhibitor of the present invention, or copolymer (A) and / or copolymer (B) added may be determined so that the concentration of copolymer (A) and / or copolymer (B) in water falls within the above range.
[0047] In the method for preventing silica-based scale adhesion of the present invention, the phosphoric acid concentration in the silica-containing water after the phosphoric acid, etc. addition step is preferably 1 to 15 mg / L, more preferably 1 to 10 mg / L. This is because the scale adhesion inhibitor of the present invention, or phosphoric acid and / or a salt thereof, is added so that the phosphoric acid concentration in the water of phosphoric acid and / or a salt thereof falls within the above range, thereby making it possible to suitably prevent the occurrence of silica-based scale in the silica-containing water. The amount of the silica-based scale adhesion inhibitor of the present invention, or phosphoric acid, etc., added may be determined so that the concentration of phosphoric acid, etc. in the water falls within the above range.
[0048] In addition, the method for preventing silica-based scale adhesion of the present invention preferably further includes a copolymer (C) addition step of adding a copolymer (C) containing (meth)acrylic acid and a structural unit represented by general formula (2). This is because the silica-based scale can be more effectively prevented by further adding the copolymer (C). The copolymer (C) is preferably an acrylic acid AMPS copolymer. In addition, when the method for preventing silica-based scale adhesion of the present invention includes a copolymer (C) addition step, the concentration of the copolymer (C) in the silica-containing water after the copolymer (C) addition step is preferably 1 to 20 mg / L, and more preferably 2 to 10 mg / L. This is because the generation of silica-based scale in the silica-containing water can be more suitably prevented by adding the scale adhesion inhibitor of the present invention or the copolymer (C) so that the concentration of the copolymer (C) in water is in the above range. In addition, the amount of the copolymer (C) added may be determined so that the concentration of the copolymer (C) in water is in the above range.
[0049] The silica-based scale adhesion inhibitor and the method for preventing silica-based scale adhesion of the present invention are preferably used to prevent adhesion of silica-based scale in a silica-containing cooling water system. Specifically, they can be preferably used to prevent scale adhesion in devices and piping such as heat exchanger bodies, circulating water pits, and cooling towers in silica-containing cooling water systems in building air conditioning, general factories, petrochemical complexes, iron ore processes, etc., and can be particularly preferably used to prevent adhesion of silica-based scale generated in silica-containing cooling water systems concentrated by reuse or circulation. Furthermore, the silica-based scale adhesion inhibitor and method for preventing silica-based scale adhesion of the present invention are preferably added to or implemented within the above-mentioned equipment (including piping) in order to prevent adhesion of silica-based scale to heat exchangers, piping, boiler water system pipes in silica-containing cooling water systems, and piping related to reinjection wells in geothermal power plants. Furthermore, the silica-based scale adhesion inhibitor and the silica-based scale adhesion prevention method of the present invention are preferably added or carried out in the above-mentioned equipment (including piping) in order to prevent adhesion of silica-based scale in heat exchangers, piping, boiler water system pipes, and piping related to reinjection wells of geothermal power plants in a silica-containing cooling water system in which the solubility of silica ions is exceeded.
[0050] The silica-based scale adhesion inhibitor and the method for preventing silica-based scale adhesion of the present invention are preferably intended for aqueous systems exceeding the solubility of silica ions, and may be intended for silica-containing aqueous systems with a silica concentration of 150 ppm or more. Also, it is preferable to use silica-containing aqueous systems with a magnesium concentration (as magnesium hardness) of 0 to 300 ppm and a calcium concentration (as calcium hardness) of 10 to 500 ppm. In such silica-containing aqueous systems, adhesion of silica-based scales has been a problem, and conventional dispersants have not been able to sufficiently prevent adhesion of silica-based scales, but the silica-based scale adhesion inhibitor and the method for preventing silica-based scale adhesion of the present invention can suitably prevent adhesion of silica-based scales. The silica-based scale adhesion preventive agent and method for preventing silica-based scale adhesion of the present invention are more preferably intended for silica-containing aqueous systems in which the solubility of silica ions is exceeded and the magnesium concentration (as magnesium hardness) is 0 to 300 ppm and the calcium concentration (as calcium hardness) is 10 to 500 ppm. The magnesium hardness is more preferably 0 to 200. The calcium hardness is more preferably 10 to 300. Water quality having silica concentration, magnesium concentration, and calcium hardness in the above-mentioned concentration ranges is prone to silica-based scale adhesion, and the conditions are severe enough that a typical silica-based scale adhesion inhibitor cannot fully prevent silica-based scale adhesion. However, the scale adhesion inhibitor and the scale adhesion prevention method of the present invention exhibit a sufficient silica-based scale adhesion prevention effect in water systems with such water quality.
[0051] Water quality containing aluminum, iron and / or zinc in the above-mentioned concentrations in addition to silica is prone to silica-based scale generation, and the conditions are severe enough that general silica-based scale deposition inhibitors are not sufficiently effective. However, even in water systems with such water quality, the silica-based scale deposition inhibitor of the present invention and the silica-based scale deposition prevention method of the present invention exhibit a sufficient silica-based scale deposition prevention effect.
[0052] The method for preventing silica-based scale adhesion of the present invention includes a copolymer addition step and a phosphoric acid or the like addition step to a silica-containing aqueous system, but the positions of the copolymer addition step and the phosphoric acid or the like addition step are not particularly limited, and may be the same or separate. That is, the copolymer (A) and / or copolymer (B) and the phosphoric acid and / or a salt thereof may be added simultaneously or separately, and the order of addition is not particularly limited. However, it is preferable to determine the addition positions of the copolymer (A) and / or copolymer (B) and the addition positions of the phosphoric acid and / or a salt thereof so that the concentration ratio of the copolymer (A) and / or copolymer (B) and the phosphoric acid and / or a salt thereof in the water added to the silica-containing aqueous system is 50:1 to 1:15. The concentration ratio of the copolymer (A) and / or copolymer (B) and the phosphoric acid in the water is more preferably 50:1 to 1:5, and even more preferably 30:1 to 1:5. Furthermore, when the method for preventing silica-based scale adhesion of the present invention includes a step of adding a copolymer and a step of adding phosphoric acid, etc. to a silica-containing aqueous system, the step of adding the copolymer and the step of adding phosphoric acid, etc. are preferably carried out at the same location. Moreover, it is preferable that the copolymer (A) and / or the copolymer (B) and the phosphoric acid and / or a salt thereof are added simultaneously.
[0053] When the method for preventing silica-based scale adhesion of the present invention includes a copolymer (C) addition step, the position of the copolymer (C) addition step is preferably determined so that the concentration ratio of the copolymer (C) added to the silica-containing aqueous system to the phosphoric acid in the silica-containing aqueous system (concentration of copolymer (C):concentration of phosphoric acid) is 20:1 to 1:20. The concentration ratio of the copolymer (C) to the phosphoric acid in the water (concentration of copolymer (C):concentration of phosphoric acid) is more preferably 15:1 to 1:15.
[0054] In the method for preventing silica-based scale adhesion of the present invention, the concentration of at least one agent selected from copolymers (A) and / or (B), phosphoric acid and / or a salt thereof, and copolymer (C) in the water in the silica-containing aqueous system is preferably measured in equipment (including piping) in the silica-containing aqueous system where silica-based scale adhesion occurs.
[0055] The scale adhesion preventive agent of the present invention can contain, in addition to copolymer (A) and / or copolymer (B) and phosphoric acid and / or a salt thereof, an anticorrosive agent, a slime control agent, an antifoaming agent, etc., as necessary. As the corrosion inhibitor, a known metal corrosion inhibitor may be used in combination within a range in which the effect of the present invention is not impaired. Examples of known metal corrosion inhibitors include organic metal corrosion inhibitors such as oxycarboxylates such as sodium succinate, sodium gluconate, and sodium malate, sugars such as glucose, and azole compounds such as benzotriazole, tolyltriazole, mercaptobenzothiazole, aminotriazole, and 2-(4-thiazolyl)benzimidazole (TBZ). Metal corrosion inhibitors such as phosphorus compounds such as phosphates, phosphonates, and polyphosphates, and heavy metal compounds such as zinc salts may also be used in combination within a range in which they do not impose a burden on the environment. When the above phosphorus compound is used in combination with the scale adhesion inhibitor or scale adhesion prevention method of the present invention, the above phosphorus compound is used to exert its effect as an anticorrosive agent within a range that does not inhibit the effect of the present invention. In other words, the phosphoric acid content weight ratio and the phosphoric acid concentration in water in the silica-containing aqueous system in the present invention described above merely define a suitable numerical range for achieving the effect of the present invention, which is to prevent adhesion of silica-based scale, and further, do not inhibit the addition of a phosphorus compound such as phosphoric acid to the scale adhesion inhibitor of the present invention in order to impart a corrosion inhibitory effect, and do not inhibit the addition of a phosphorus compound such as phosphoric acid in the scale adhesion prevention method of the present invention. As the slime control agent and the defoaming agent, known compounds may be used in combination within the range that does not impair the effects of the present invention.
[0056] In yet another embodiment, the present invention may be a water treatment agent comprising copolymer (A) and / or copolymer (B), and phosphoric acid and / or a salt thereof, wherein the copolymer (A) is a copolymer containing (meth)acrylic acid, a structural unit represented by the following general formula (1), and a structural unit represented by the following general formula (2), and the copolymer (B) is a copolymer containing (meth)acrylic acid and a structural unit represented by the following general formula (1). The scale inhibitor of the present invention exhibits a remarkable silica-based scale inhibitory effect in silica-containing aqueous systems (particularly aqueous systems in which the solubility of silica ions is exceeded), and since it contains phosphoric acid and / or a salt thereof, in addition to the silica-based scale inhibitory effect, it also exhibits an anti-corrosion effect on metals, thereby exhibiting excellent water treatment effects.
[0057] The water treatment agent of the present invention may further contain a zinc salt. In silica-containing water systems, the corrosion of metals in contact with water is also a major problem, along with the problem of scale adhesion. It is generally known that zinc salts are very effective as corrosion inhibitors for carbon steel, but in silica-containing water systems that exceed the solubility of silica ions in water (for example, silica-containing water systems with a silica concentration of more than 150 ppm at 25° C.), there is a problem that zinc salts promote the adhesion of silica-based scale, and therefore a sufficient amount of zinc salt cannot be added. On the other hand, the water treatment agent of the present invention can prevent the deposition of silica-based scale even in silica-containing aqueous systems that exceed the solubility of silica ions in water (for example, silica-containing aqueous systems in which the silica concentration exceeds 150 ppm at 25° C.) Therefore, by further containing a zinc salt, it is possible to obtain a sufficient corrosion inhibition effect on carbon steel while sufficiently suppressing the deposition of silica-based scale. EXAMPLES
[0058] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0059] The evaluation of silica-based scale damage was performed using the evaluation method described in Japanese Patent No. 6387502. FIG. 1 is a schematic diagram of a cooling water system used in the evaluation of silica-based scale damage. Raw water (tap water from Oita City) was passed through a reverse osmosis membrane device to prepare silica-containing water with a silica concentration of about 300 ppm, and the chemicals listed in Table 1 below were added to the obtained 300 ppm silica-containing water. The evaluation water containing the chemicals was brought into contact with a double-tube test column 4 for 5 days to perform a double-tube evaluation test to evaluate silica-based scale damage. The hot water temperature in the double-tube evaluation test was 80°C. In the double-tube evaluation test, the occurrence of silica-based scale damage was evaluated in the heat transfer section where the temperature of the evaluation water was 50°C. The 300 ppm silica-containing water obtained from the reverse osmosis membrane device had a silica concentration of about 300 ppm, Ca hardness of about 190 ppm, and Mg hardness of about 110 ppm. The total silica concentration (ppm) in the evaluation water differs for each test, so the total silica concentration for each test is shown in Table 1 below.
[0060] (Drugs) Copolymer (A): Acrylic acid / N-tert-butylacrylamide / 2-acrylamido-2-methylpropanesulfonic acid (AMPS) copolymer (Distributor: Dow Chemical Japan Co., Ltd. Product number: ACUMER TM 5000) Copolymer (C): AMPS acrylate (sold by Toa Gosei Co., Ltd., Aron A-6012) Phosphoric acid: (Sold by Kishida Chemical Co., Ltd.) Potassium pyrophosphate: (Sold by Fujifilm Wako Pure Chemical Industries, Ltd.) Sodium hexametaphosphate: (Sold by Fujifilm Wako Pure Chemical Industries, Ltd.) PBTC
[0061] (Criteria for determining silica scale damage) ○: No scale buildup is observed. And 1 cm per month 2 Scale amount per unit (MCM / mg / cm 2 ·month) is less than 3. ×: Scale adhesion is observed over the entire surface, or MCM is 3 or more. The presence or absence of scale adhesion was confirmed visually. The results obtained are shown in Table 1 below.
[0062] [Table 1]
[0063] From the results of Examples 1 to 6 in Table 1 above, a sufficient silica-based scale adhesion prevention effect was obtained by adding an agent containing copolymer (A) and phosphoric acid to silica-containing water having a silica concentration of 200 to 310 ppm. Moreover, the results of Examples 7 to 13 show that an excellent effect of preventing adhesion of silica-based scale was obtained by using the copolymer (A), phosphoric acid, and the copolymer (C). On the other hand, the results of Comparative Example 2 show that copolymer (A), which is known as a silica-based scale adhesion inhibitor, alone cannot provide a sufficient silica-based scale adhesion inhibitory effect for silica-containing water having a silica concentration of 310 ppm. Furthermore, the results of Comparative Examples 3 and 9 show that even when an agent containing copolymer (A) and copolymer (C) was added, the effect of preventing silica-based scale adhesion could not be obtained for silica-containing water having a silica concentration of 300 ppm. Furthermore, the results of Comparative Examples 4, 5 and 8 show that even when an agent containing copolymer (A) and a phosphorus compound was added, the effect of preventing the adhesion of silica-based scale could not be obtained in silica-containing water having a silica concentration of 300 ppm. Furthermore, the results of Comparative Examples 6 and 7 show that even when an agent containing copolymer (A), a phosphorus compound, and copolymer (C) was added, the effect of preventing silica-based scale adhesion could not be obtained for silica-containing water having a silica concentration of 300 ppm. That is, it was confirmed that a sufficient silica-based scale adhesion prevention effect can be obtained in a silica-containing aqueous system where silica-based scale is likely to occur by combining a specific copolymer (copolymer (A)) with phosphoric acid and / or a salt thereof. Note that, in the examples, no scale was adhered, or even if scale was adhered, the amount was very small, so that it was not possible to measure the constituent elements of the adhered scale.
[0064] Although the total silica concentration (ppm) in the evaluation water differed for each test, in each test the test water contained calcium ions and magnesium ions, which react with silica to form scale, and in the double-walled pipe evaluation test in which hot water at 80°C flows, the temperature of the heat transfer part of the metal surface was close to 80°C, and furthermore, the pH condition of the test water was 8.4 to 8.5, making the conditions very favorable for the formation of silica-based scale. This test confirmed that a sufficient silica-based scale adhesion prevention effect could be obtained even in silica-containing water systems where silica-based scale is likely to form. Furthermore, in the above-mentioned Examples 1 to 13, the test water after the test was not cloudy. The generation of amorphous silica can be confirmed by the presence or absence of cloudiness in the silica-containing water system, and the generation of silicate scale can be confirmed by the presence or absence of scale adhesion to the heat transfer surface. Since neither of these was confirmed, it was confirmed that the agent containing copolymer (A) and phosphoric acid in Examples 1 to 6, and the agent containing copolymer (A), phosphoric acid, and copolymer (C) in Examples 7 to 13 were all able to sufficiently prevent the adhesion of silica-based scale (amorphous silica and silicate scale). In Comparative Examples 1, 4 to 6, and 8 to 10, the test water was not cloudy after the test, but scale adhesion occurred on the heat transfer surface. In Comparative Examples 2, 3, and 9, the test water was cloudy after the test, and scale adhesion occurred on the heat transfer surface. That is, silicate scale was generated and adhered in all of Comparative Examples 1 to 9. Furthermore, from the results of Comparative Examples 1, 4 to 6, and 8 to 10, even when the test water did not become turbid, silicate scale adhered to the heat transfer surface, and therefore it can be said that suppressing turbidity in silica-containing water systems (by improving the solubility of silica ions in the water or suppressing the precipitation of silica scale in the water) does not necessarily lead to prevention of the adhesion of silica-based scale.
[0065] Although a test using a drug containing copolymer (B) and phosphoric acid and / or a salt thereof was not conducted due to the availability of copolymer (B), in the technical field to which the present invention pertains, the above-mentioned copolymer (A) and copolymer (B) are expected to exhibit similar effects, and therefore it is considered that the same effects will be exhibited even when copolymer (A) is replaced with copolymer (B). Therefore, it is considered that a sufficient silica-based scale adhesion prevention effect can be obtained in silica-containing aqueous systems by combining a specific copolymer (copolymer (B)) with phosphoric acid and / or a salt thereof. [Explanation of symbols]
[0066] 1 Test water pit 2. Water pump 3 Flowmeter 4 Test Column 5. Test Tubes
Claims
1. Contains a copolymer (A) and phosphoric acid and / or a salt thereof, The copolymer (A) is a copolymer containing (meth)acrylic acid, a structural unit represented by the following general formula (1), and a structural unit represented by the following general formula (2): A silica-based scale adhesion inhibitor characterized by: 【Chemistry 1】 (In the formula, R 1 is H or COOX, X is H or a metal cation, R 2 and R 3 is H or C 1-8 The alkyl groups can be either H or CH. 3 It is.) 【Chemistry 2】 (Wherein, R is H or CH 3 X is H or a metal cation; R 4 is C 1-8 is an alkyl group or a phenyl group, and R 5 is H or C 1-4 is an alkyl group.
2. 2. The silica-based scale inhibitor according to claim 1, wherein the weight ratio of the copolymer (A) to phosphoric acid and / or a salt thereof is from 50:1 to 1:
5.
3. Further comprising a copolymer (C), The silica-based scale adhesion preventive agent according to claim 1 or 2, wherein the copolymer (C) is a copolymer containing (meth)acrylic acid and a structural unit represented by the following general formula (2) and not containing a structural unit represented by the following general formula (1): 【Chemistry 3】 where R 1 is H or COOX, X is H or a metal cation, R 2 and R 3 are either H or a C 1-8 alkyl group, but cannot both be H, and R is H or CH 3 . 【Chemistry 4】 wherein R is H or CH 3 , X is H or a metal cation, R 4 is a C 1-8 alkyl group or a phenyl group, and R 5 is H or a C 1-4 alkyl group.
4. A method for preventing silica-based scale deposition, comprising using the silica-based scale deposition inhibitor according to claim 1 or 2 in a silica-containing aqueous system.
5. The method includes a copolymer adding step of adding a copolymer (A) to a silica-containing aqueous system, and a phosphoric acid or the like adding step of adding phosphoric acid and / or a salt thereof, The copolymer (A) is a copolymer containing (meth)acrylic acid, a structural unit represented by the following general formula (1), and a structural unit represented by the following general formula (2), The silica-containing aqueous system has a silica concentration of more than 150 ppm at 25° C. A method for preventing silica-based scale adhesion, comprising: 【Chemistry 5】 (In the formula, R 1 is H or COOX, X is H or a metal cation, R 2 and R 3 is H or C 1-8 The alkyl groups can be either H or CH. 3 It is.) 【Chemistry 6】 (Wherein, R is H or CH 3 X is H or a metal cation; R 4 is C 1-8 is an alkyl group or a phenyl group, and R 5 is H or C 1-4 is an alkyl group.
6. The method for preventing silica-based scale adhesion according to claim 5, wherein a weight ratio of the copolymer (A) added in the copolymer adding step to the phosphoric acid and / or a salt thereof added in the phosphoric acid etc. adding step is 50:1 to 1:
5.
7. 7. The method for preventing silica-based scale adhesion according to claim 5 or 6, wherein in the phosphoric acid or the like addition step, phosphoric acid and / or a salt thereof is added so that the ratio of silica concentration to phosphoric acid concentration (silica concentration:phosphoric acid concentration) in the silica-containing aqueous system is 25:1 to 300:
1.
8. The method for preventing silica-based scale adhesion according to claim 5 or 6, further comprising a copolymer (C) adding step of adding a copolymer (C) which contains (meth)acrylic acid and a structural unit represented by the following general formula (2), but does not contain a structural unit represented by the following general formula (1). 【Chemistry 7】 where R 1 is H or COOX, X is H or a metal cation, R 2 and R 3 are either H or a C 1-8 alkyl group, but cannot both be H, and R is H or CH 3 . 【Chemistry 8】 wherein R is H or CH 3 , X is H or a metal cation, R 4 is a C 1-8 alkyl group or a phenyl group, and R 5 is H or a C 1-4 alkyl group.
Citation Information
Patent Citations
JP1851103B
Silica scale preventing agent
JP1983084098A
Corrosion suppressing composition containing acrylic acid / 2-acryamide-2-methylproplylsulfonicacid polymer
JP1986125497A
Agent for preventing scaling in cooling water system
JP1990031894A
Scaling inhibitor and method for preventing scaling
JP2003080294A